Preparation and characterization of octadecane/polyurea nanocapsule‐embedded poly(ethylene oxide) nanofibers. Issue 37 (12th June 2015) - Kook, Jun‐Won; Cho, Wonseok; Koh, Won‐Gun; Cheong, In Woo; Kim, Jung Hyun
ABSTRACT This article describes the preparation and characterization of latent heat storage poly(ethylene oxide) nanofibers (LHS‐PEO nanofibers) with octadecane/polyurea (PCM/PU) nanocapsules. PCM/PU nanocapsules were prepared by interfacial polycondensation from toluene 2, 4‐diisocyanate and ethylene diamine in a resin‐fortified emulsion system. LHS‐PEO nanofibers were prepared using an electrospinning procedure with varying PCM/PU nanocapsules content, i.e., from 0 to 8 wt %. The PCM/PU nanocapsules were polydisperse with an average diameter of 200 nm. The melting and freezing temperatures were determined as 23.7 and 28.2°C, respectively, and the corresponding latent heats were determined as 123.4 and 124.1 kJ kg−1, respectively. The encapsulation efficiency of the PCM/PU nanocapsules was 78.1%. The latent heat capacity of the LHS‐PEO nanofibers increased as the PCM/PU nanocapsules content increased. Defects, such as holes and disconnection of the nanofibers, were observed, particularly inside the LHS‐PEO nanofibers. For packaging applications, mats were fabricated from the nanocapsules‐embedded nanofibers with varying nanocapsule content and the mats' surface temperatures were monitored with a thermal imaging camera. The results proved the feasibility of using the LHS‐PEO nanofibers for thermal energy storage and functional packaging materials. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42539.